Economic Analysis Of Flare Gas Utilization For Electric Power Generation In PT. CPI (The Indonesian Journal of Business Administration, 2021)
For generating electric power, PT CPI purchases gas from the third party for fuel in large portion beside utilize own gas from several gas production facilities. There is opportunity to reduce operating expenditure for gas purchasing by utilization of Alfa & Beta flare gas. For the years, associated gas production in Alfa and Beta stations were flared and have not been utilized for any economic purpose. Total cost to produce electric power by executing new proposal will be compared with existing condition. This research used a quantitative approach (capital budgeting) with data sources include associated gas production forecasts from the subsurface team, gas composition analysis from lab team, cost estimation by using the unit price of the current contract, and lessons learned from previous similar projects. As example, lesson learned about how many required manpower for engineering design, construction management or project management cost in previous similar projects. Alfa and Beta Flare Gas Recovery facilities will be built to process and deliver flare gas from these 2 stations to Pager Gas Plant (GP). In Pager GP, existing gas compressors deliver gas to Duri Power Plant, to be used further as fuel of power generators. On the other hand, capital investment and additional operational costs are needed for routine operation & maintenance activities, compressor overhaul, electric power, pipeline maintenance, chemical injection, and others. In terms of project feasibility analysis, cost-saving PV is $916,386, with IRR = 23%, and the payback period of investment is 1,8 years. By considering the analysis above, it’s concluded that Alfa and Beta Flare Gas Utilization is economically feasible and it’s recommended to execute soon when the Riau block is already handed over from PT CPI to PT PTM in 2021. By conducting sensitivity analysis, it’s concluded that the parameters that have the most impact on the variance of project economic result are gas production forecast (% decline rate), continued by gas price forecast ($/MMBTU), and continued by capital expenditure ($). By knowing this result, project team can pay attention more on validity of gas production forecast as the most influencing factor to project economic.Keywords: Flare Gas, Power Generator Fuel, Project Feasibility, Cost Saving